Answer:
The distance between (-2 1/2, -3) and (1, -3) will be:
Step-by-step explanation:
Given the points
[tex]\mathrm{Convert\:mixed\:numbers\:to\:improper\:fraction:}\:a\frac{b}{c}=\frac{a\cdot \:c+b}{c}[/tex]
[tex]-2\frac{1}{2}=-\frac{5}{2}[/tex]
so the point becomes (-5/2, -3)
Finding the distance between (-5/2, -3) and (1, -3):
[tex]\mathrm{Compute\:the\:distance\:between\:}\left(x_1,\:y_1\right),\:\left(x_2,\:y_2\right):\quad \sqrt{\left(x_2-x_1\right)^2+\left(y_2-y_1\right)^2}[/tex]
[tex]\mathrm{The\:distance\:between\:}\left(-\frac{5}{2},\:-3\right)\mathrm{\:and\:}\left(1,\:-3\right)\mathrm{\:is\:}[/tex]
[tex]d=\sqrt{\left(1-\left(-\frac{5}{2}\right)\right)^2+\left(-3-\left(-3\right)\right)^2}[/tex]
[tex]=\sqrt{\left(\frac{5}{2}+1\right)^2+\left(3-3\right)^2}[/tex]
[tex]=\sqrt{\frac{7^2}{2^2}+0}[/tex]
[tex]=\sqrt{\frac{7^2}{2^2}}[/tex]
[tex]\mathrm{Apply\:radical\:rule\:}\sqrt[n]{\frac{a}{b}}=\frac{\sqrt[n]{a}}{\sqrt[n]{b}},\:\quad \mathrm{\:assuming\:}a\ge 0,\:b\ge 0[/tex]
[tex]=\frac{\sqrt{7^2}}{\sqrt{2^2}}[/tex]
[tex]\mathrm{Apply\:radical\:rule\:}\sqrt[n]{a^n}=a,\:\quad \mathrm{\:assuming\:}a\ge 0[/tex]
[tex]=\frac{7}{2}[/tex]
Thus, the distance between (-2 1/2, -3) and (1, -3) will be: